Nurse Perceptions and Satisfaction of Assessments Competencies Process: A Cross Sectional Study - Hariyati, Rr.Tutik Sri; Handiyani, Hanny; Setyowati, Setyowati; Sukihananto, Sukihananto; Purwaningsih, Sri; Sugihasih, Sugihasih (Jurusan Keperawatan FIKES UNSOED, 2020)
Professional Competency is a topic of great issues in care and practice, particularly health care disciplines such as nursing. Nursing competence is the ability to demonstrate knowledge, skill, professional attitude and ability to take a clinical decision practice. The purpose of the study was explored nurse perception of a competencies assessment process. Data were collected using a questionnaire and involved a proportional random sample of 410 nurses practitioner.Â They were analyzed using descriptive statistical methods: mean, median and standard deviation. Result: Many nurses not satisfied taken assessment competencies using examination approach and summative by assessor (mean: 48.07, SD: 4.7, CI: 47.6-48.52) andÂ education background correlated significant with satisfaction, in while BN has lower satisfaction than Diploma (Dip:48.35; BN:47.1; p=0.18)Â Conclusion and Implication: many nurses felt unsatisfied using examination and summative assessment approach and better for management to evaluate of process and improve assessment competency process. Ongoing professional performance evaluation (OPPE) can be developed to improve the competency evaluation